Modulation of the Endothelin System in Colorectal Cancer Liver Metastasis: Influence of Epigenetic Mechanisms? - Mahdi, Mohamed R.; Georges, Rania B.; Ali, Doaa M.; Bedeer, Raouf F.; Eltahry, Huda M.; Gabr, Abd-El Hakiem Z.; Berger, Martin R. (Frontiers in Pharmacology, 2020)
Targeting of endothelin system genes is a promising strategy in cancer therapy. The modulation of these genes was explored during colorectal cancer (CRC) liver metastasis and in vitro, when a panel of CRC tumor cell lines was exposed to the demethylating agent decitabine. The CC531 rat model mimicking CRC liver metastasis was used for tumor cell re-isolation and analysis of the endothelin system genes and DNA methyltransferases (DNMTs) by microarray. To mimic the effects caused by methylation changes, a panel of seven CRC cell lines was treated with the demethylating agent decitabine. Three genes of the endothelin system were intensively modulated at mRNA level in rat CC531 cells during liver colonization. An influence from altered methylation was suggested by the concomitant decrease of two DNMTs. Changes in gene expression were also accomplished by exposure of CRC cells to the demethylating agent decitabine, when using daily low concentrations for three days, at minimal cytotoxic side effects. Sensitive human SW480 cells showed an almost 100fold upregulation of endothelin-1 mRNA compared to untreated cells. This, however, was different in LS174T cells, which showed no significant increase in gene expression although the methylation levels were significantly decreased at a variety of corresponding loci. It is derived that the mechanism exerted by methylation on gene expression in metastatic CRC cells can be compromised. The results question the overall success of treating metastatic CRC by methylation inhibitors.